2012
DOI: 10.1002/adfm.201201025
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Origins of Nonlinear Behavior in Ferroic Thin Films

Abstract: The nonlinear response of a ferroic to an applied field has been studied through the phenomenological Rayleigh Law for over a hundred years. Yet, despite this, the fundamental physical mechanisms at the nanoscale that lead to macroscopic Rayleigh behavior have remained largely elusive, and experimental evidence at small length scales is limited. Here, it is shown using a combination of scanning probe techniques and phase field modeling, that nanoscale piezoelectric response in prototypical Pb(Zr,Ti)O3 films ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Experiments have focused primarily on the latter, more accessible regimes, using piezoresponse force microscopy (PFM) to image needle-like [8] or cylindrical [9] domains in single crystals and thin films. Such studies have demonstrated the creep-like lateral motion of domain walls pinned by defects [10][11][12], recently confirmed with atomic resolution by direct imaging of domain growth using transmission electron microscopy [13]. They also highlighted the crucial role of surface adsorbates [14][15][16][17], particularly water, which determine the electrostatic boundary conditions and thus the size, shape and growth rate of the domain [18][19][20].…”
Section: Introductionmentioning
confidence: 94%
“…Experiments have focused primarily on the latter, more accessible regimes, using piezoresponse force microscopy (PFM) to image needle-like [8] or cylindrical [9] domains in single crystals and thin films. Such studies have demonstrated the creep-like lateral motion of domain walls pinned by defects [10][11][12], recently confirmed with atomic resolution by direct imaging of domain growth using transmission electron microscopy [13]. They also highlighted the crucial role of surface adsorbates [14][15][16][17], particularly water, which determine the electrostatic boundary conditions and thus the size, shape and growth rate of the domain [18][19][20].…”
Section: Introductionmentioning
confidence: 94%
“…This provides direct experimental evidence of the nanoscale origins of enhanced piezoelectric response in mixed-phase BFO. Furthermore, this approach can be extended to other polycrystalline and polydomain ferroelectrics in order to grasp the role of such extrinsic contributors [19][20][21][22][23] in their electromechanical response. Figure 1 outlines the possible sources of enhancement including interfacial mechanisms, i.e., reversible and irreversible motion of phase boundaries, 24 and lattice contributions arising from polarization rotation 25,26 or electrostriction.…”
mentioning
confidence: 99%
“…Recently we have shown that the individual behavior of domain walls in ferroelectrics at the local level is different from that expected from the traditional Rayleigh framework11. Here, a new SPM technique using n th order harmonic detection and band-excitation is demonstrated that allows decoupling of responses in microscale volumes.…”
mentioning
confidence: 88%
“…Furthermore, the third and higher order harmonic terms are characterized by a quadratic dependence of the strain on the driving field22. In many ferroelectrics, extrinsic contributions to the piezoelectric coefficients arise primarily from the motion of ferroelastic domain walls4211. However, certain samples in which ferroelastic walls were not active still exhibited a linear dependence of the piezoelectric coefficient on the driving field43.…”
mentioning
confidence: 99%
See 1 more Smart Citation